Third Streptococcus pneumoniae disease outbreak involving serotype 4–ST801 in a shipyard, Finland, May to June 2025 - Manca, Maria Francesca; Silvola, Jaakko; Czarnecki, Jakub; Sequeira Neto, Joana; Kanerva, Mari; Kaukavuori, Heikki; González Pérez; Ana Cristina; Lindström, Irmeli; Frilander, Heikki; Fomichev, Mikhail; Marttila, Harri; et al. (European Centre for Disease Control and Prevention (ECDC), 2026)
Finland experienced three invasive pneumococcal disease (IPD) outbreaks among shipyard workers at the same shipyard, in 2019, 2023 and 2025. During the latest outbreak (30 April-6 June 2025), 13 cases were reported, with six confirmed. All five isolates from blood culture-positive cases were serotype 4 - sequence type 801. These were nearly indistinguishable from three isolates from the 2019 outbreak, nine Finnish IPD surveillance isolates and isolates of a 2019 Norwegian shipyard outbreak. We found an association with welding.